Effect of an Educational Intervention on Quality of Life and Sexual Function in Women with Endometriosis (International Journal of Studies in Nursing, 2018)
Aim of the study was to investigate the effect of an educational intervention on quality of life and sexual function in women with endometriosis. Design: Quasi experimental time series research design. Setting: obstetrics and gynecology outpatient clinic affiliated to Benha University Hospital and Benha teaching Hospital. Sample: A purposive sample of 138 women diagnosed with endometriosis was eligible in the study and assigned equally into study and control groups. Tools for data collection: A structured interviewing questionnaire, Endometriosis Health Profile Questionnaire-30 and Sexual Health Outcomes in Women Questionnaire. Results: There was no statistically significant difference between both groups regarding demographic and obstetrical characteristics (p ˃ 0.05). Before implementation of educational intervention, the mean scores of total EHP-30 and SHOW-Q showed impaired quality of life and sexual function in the both groups (p ˃ 0.05). After one and two months of educational intervention implementation, mean total score of EHP-30 was significantly lowered in the study group compared with the control group. The mean scores of satisfaction, orgasm, and desire subscales were significantly higher in study group compared with control group. Whereas, the mean score of the pelvic problem interference subscale was significantly lower in study group compared with control group (p ≤ 0.001). Conclusion: The educational intervention about endometriosis has significant effect on the improvement of women's quality of life and sexual function. Recommendation: Provide health educational program for women with endometriosis to improve quality of life as well as sexual function.